Abundancia del gato montés (Lynx rufus escuinapae J. A. Allen, 1903) en el Parque Nacional el Cimatario, Querétaro, México - López-González, Carlos A.; Ávila Aguilar, Daniel; Cruz-Torres, María Fernanda (Instituto de Ecología, A.C., 2015)
Bobcat conservation status in central Mexico remains unclear. In many localities it is possible that bobcat populations are declining, so it is very important to estimate the densities of this species. In this note we report an abundance of 3 ± 0.78 bobcats and a minimum density of 0.17 ind/km2 at the Parque Nacional El Cimatario, Querétaro. Information on the species is limited and this data are needed to improve our knowledge in fragmented landscapes.